Na obrzeżu społeczności z obrzeży świata egejskiego, czyli akty wyzwoleń niewolników na Krecie w epokach hellenistycznej i rzymskiej - Pałuchowski, Adam (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
This paper will deal, mainly, with two manumission inscriptions found in the 1950s during excavations of the Asklepieion at Lissos and recently published by Martha W. Baldwin Bowsky. Their paleographically supported dating, broadly fixed by the editor princeps at the second century AD, may be refined to the reign of Hadrian thanks to comparison with regional, west-Cretan epigraphic evidence. At first glance, they seem to reflect no more than certain features of Cretan slavery specifically related to a new socio-economic framework in Imperial times, when the island was entirely integrated into an enormous pacified commercial area in the Roman Empire. But if we attempt to consider them in connection with minor epigraphic testimony uncovered towards the end of the 19th century in Anopolis (ICret II.2 1), a small city located some thirty kilometres eastward from Lissos, a completely different insight becomes possible. The latter, paleographically dated to the first century BC, is quite a puzzling epitaph: although its onomastics, including patronymic filiation, is purely Greek, it simultaneously reveals Roman lexical and conceptual influence by use of the Latin word patronus, transliterated into the Greek πάτρων. Such a common term belonging to the Roman social register would betray a client-patron relationship, largely corresponding to the paramonerelationship established in the Greek world between a freedman/freedwoman and his/her former master/mistress in the wake of manumission, and as a kind of useful prolongation of his/her previous servile status. If so, one should probably approach the epitaph against the background of the disruption of Cretan slavery patterns at the end of the second century BC, when communal slavery (i.e. serfdom) definitively disappears all over the island, due to a profound and relatively rapid modification of its socio-economic conditions. Seen in this light, both the epitaph from Anopolis and the two manumission inscriptions from Lissos would demonstratea local adaptation to disturbances which occurred just before the island fell under the power of the Romans.
Keywords: Kreta; niewolnictwo kreteńskie; Asklepieion w Lissos; wyzwolenie niewolnika przez poświęcenie bóstwu; paramone